A modified FOX-1 method for Micro-determination of hydrogen peroxide in honey samples. (15th December 2017) - Li, Dan; Wang, Meng; Cheng, Ni; Xue, Xiaofeng; Wu, Liming; Cao, Wei
Highlights: A modified FOX-1 method for micro-determination of hydrogen peroxide in honey samples was established for the first time. The proposed method was confirmed to be sensitive, accurate and precise through methodology validation. The levels of hydrogen peroxide in 35 honey samples from 5 floral origins were evaluated. Abstract: Hydrogen peroxide (H2 O2 ) is a major antibacterial activity-associated biomarker in honey. Measurement of endogenous H2 O2 in honey is of great value in prediction of the H2 O2 -depended antibacterial activity and characterization or selection of honey samples for their use as an antibacterial agent or natural food preservative. Considering current methods for H2 O2 determination are either time-consuming or complicated with their high-cost, a study was conducted to modify and validate the spectrophotometry-based ferrous oxidation-xylenol orange (FOX-1) method for micro-determination of H2 O2 in honey samples. The result suggested that the proposed FOX-1 method is fast, sensitive, precise and repeatable. The method was successfully applied for the analysis of a total of 35 honey samples from 5 floral origins and 33 geographical origins. The proposed method is low-cost and easy-to-run, and it can be considered by researchers and industry for routine analysis.